2012
DOI: 10.4172/2155-9546.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Partial Replacement of Dietary Animal Protein from Plant Protein Blended with Glucosamine on Growth and Body Indices of Asian Catfish (Clarias Batrachus) Fingerlings

Abstract: A 12-week feeding trials was conducted to evaluate the use of animal and plant protein, in combination with Glucosamine source for Asian Catfish, Clarias batrachus (av. wt. 2.2+0.009 to 2.6+0.03 g). This study was performed to evaluate the effect on fish growth performance by replacing animal protein with vegetable protein sources. In experiment, six (37.40 to 43.52 % crude protein, 16.15 to 16.76 kJ/g energy, and crude lipid 3.33 to 6.69%) practical diets were formulated. The animal and plant protein componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, salinity affects the growth and survival of the magur fingerlings; growth rate was directly affected by increasing salinity concentration (Sahoo, Giri, Maharathi, & Sahu, ; Sarma, Prabakaran, Krishnan, Grinson, & Kumar, ). The animal protein diet fed juveniles of C. batrachus attained the body weight of 12.5 g than the plant protein diet (Chowdhary et al, ). All reported studies had both lower or similar body length and weight as compared to the present findings which strongly suggest that the length–weight relation of the present study can be used to assess the growth of C. magur in captive and wild condition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, salinity affects the growth and survival of the magur fingerlings; growth rate was directly affected by increasing salinity concentration (Sahoo, Giri, Maharathi, & Sahu, ; Sarma, Prabakaran, Krishnan, Grinson, & Kumar, ). The animal protein diet fed juveniles of C. batrachus attained the body weight of 12.5 g than the plant protein diet (Chowdhary et al, ). All reported studies had both lower or similar body length and weight as compared to the present findings which strongly suggest that the length–weight relation of the present study can be used to assess the growth of C. magur in captive and wild condition.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean products as dietary protein source has been reported to affect the growth and feed utilization of many fish species including channel catfish [46,47], tilapia [24,48], rainbow trout [49,66,68,69], red drum [67,70], seabream [71], Asian catfish [27], cobia [72] and cuneate drum [73]. Amongst the animal proteins, fish meal, meat-meal, goat liver, fish and poultry offal's used as fish diet in case of catfishes particularly in C. batrachus, fish meal has always been considered to perform better in terms of survival, growth and general well-being [74,75,76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the dietary requirement of protein is different in various fish species [20,21,22,23,24] reported that partial replacement of FM protein with SBM protein in tilapia diet did not compromise growth of the fish. Substitution of various soy products have shown better growth in many fishes including catfishes [8,25,26,27]. Recently, Sarowar et al [28] have studied the impacts of different diets on survival and growth in C. batrachus grow-outs.…”
Section: * Corresponding Author Email : Ppsicar@gmailcom Fax +91-22mentioning
confidence: 99%